A review on Silicide based materials for thermoelectric applications - Singh, Sarabjeet; Sharma, Yogesh Chandra (International Journal of Advanced Engineering Research and Science, 2021)
Thermoelectric materials are considered prime in converting energy, thanks to its nature to translate heat into electricity openly. Low efficiency and the intricacy in fabrication restrict their applications commercially. Moreover, there are certain thermoelectric materials such as alloys of telluride owing to their toxicity present peril to the environment. There is scarcity in present examination to get an ecological gracious thermoelectric material which is available in abundance to be utilized in large volumes owing to the low efficiency. The paper presents a review of such thermoelectric material which is ecological gracious. In the beginning, a number of techniques employed in advancing the figure of merit (ZT) is offered, then an in -depth review of several thermoelectric materials which are silicon-based is showed. N-type doping of Mg2Si0.75Sn0.25 among aluminum along with lead at operational temperature of 850 K scaled up the value of ZT by a factor of 2. Considerable addition in carrier concentration resulted in the attainment of figure of merit with peak value of 1.4. Techniques such as nanostructuring and doping have boosted silicides such as HMS to show a remarkable achievement in the attainment of dimensionless figure of merit. Iron disilicide (FeSi2), Chromium silicide (CrSi2) and Cobalt Silicide (CoSi) have shown their worth to be employed as thermoelectric materials in industries in near future. It is also recommended to analyze supplementary types of metal oxides and organic materials which exhibit thermoelectric traits.